Amplification mechanism with interacting atomic gases - Min Jiang; Yushu Qin; Yuanhong Wang; Ying Huang; Xinhua Peng; Dmitry Budker (Proceedings of the National Academy of Sciences, 2025)
The use of atoms, molecules, and free electrons in quantum amplifiers has greatly advanced precision measurements, paving the way for the development of extremely-low-noise quantum devices such as masers and lasers. Here, we investigate the signal amplification of interacting spins and observe the amplification of magnetic fields using mixtures of interacting alkali-metal and noble gases. In contrast to noninteracting systems used as amplifiers, we demonstrate that interactions resulting from random atomic collisions give rise to two distinct amplification phenomena. These phenomena provide essential resources for enhancing quantum sensing capabilities. Our results show that magnetic fields can be amplified by at least two orders of magnitude, enhancing magnetic sensitivity to the femtotesla per root hertz level. Additionally, we report a counterpart phenomenon, deamplification, where the magnetic noise response is suppressed by at least one order of magnitude within certain frequency regimes. In this work alkali-metal and noble-gas spins are weakly coupled. We further explore how the performance of amplification changes with the interaction strength as the two spin gases gradually enter the strong-coupling regime, unveiling hitherto unexplored amplification effects that hold promise for enhancing precision measurements.